4t-2-2t-7=

Simple and best practice solution for 4t-2-2t-7= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4t-2-2t-7= equation:


Simplifying
4t + -2 + -2t + -7 = 0

Reorder the terms:
-2 + -7 + 4t + -2t = 0

Combine like terms: -2 + -7 = -9
-9 + 4t + -2t = 0

Combine like terms: 4t + -2t = 2t
-9 + 2t = 0

Solving
-9 + 2t = 0

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + 2t = 0 + 9

Combine like terms: -9 + 9 = 0
0 + 2t = 0 + 9
2t = 0 + 9

Combine like terms: 0 + 9 = 9
2t = 9

Divide each side by '2'.
t = 4.5

Simplifying
t = 4.5

See similar equations:

| 5(2x-9)=2(x-8)-11 | | 8-b=7v | | (-5+5n)(-6)-(7-4d)(-2)= | | -3(-4y+u)-5(-6u-6y)= | | 1.8b=0.9 | | 8(2)=3(x+3) | | 8(x-3)=6x+11-5x | | 42+22x=180 | | 13x+9x-8+50=180 | | 5x+90=2x-15 | | (32x-7y)-(28x-11y)=0 | | 1.6h+72=4h-30 | | -30x^2+35x-10=0 | | -4.42x+.9=-9.070-0.432 | | 11x-10y=30 | | 60+.50(200)=1.30(200) | | 20x-9(3)=7 | | 19+[3x(7-3)]-2= | | .5(-4x-5)=7x-.5 | | 3x^3-3x^6-9x^3+5=0 | | 65-85=x | | (x-1)(2x)(x-4)=40 | | 5d-33=7.2 | | 32x=5x-14 | | r/3-4=3 | | 3x-(2x-1)=5x+1-4x | | 60+.50(100)=1.30(100) | | -5.26+.21x=19.94 | | 7cos(7x)=0 | | 16x^2-4x+5-(16x^2-8x)+1=0 | | -12x-11=-47 | | 7(-8x)= |

Equations solver categories